2017
DOI: 10.3389/fcimb.2017.00104
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Entanglement: Neutrophil Extracellular Traps (NETs) in Cystic Fibrosis

Abstract: Cystic fibrosis (CF) is an autosomal recessive disorder caused by mutations in the gene that codes for the CF trans-membrane conductance regulator. These mutations result in abnormal secretions viscous airways of the lungs, favoring pulmonary infection and inflammation in the middle of neutrophil recruitment. Recently it was described that neutrophils can contribute with disease pathology by extruding large amounts of nuclear material through a mechanism of cell death known as Neutrophil Extracellular Traps (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 69 publications
0
44
0
1
Order By: Relevance
“…Although NETs have potentially beneficial anti-pathogenic functions in respiratory host defenses, protection can easily turn to injury when extensive, unbalanced NET formation occurs. NETs are embedded with potent granule proteins that are capable of killing pathogens but may also, under the right conditions, induce cell death of lung epithelial and endothelial cells (27) and contribute to certain lung diseases such as asthma (28), cystic fibrosis (29), and COPD (30). Little is known regarding the interaction between NETs and specific cells, including AMs.…”
Section: Discussionmentioning
confidence: 99%
“…Although NETs have potentially beneficial anti-pathogenic functions in respiratory host defenses, protection can easily turn to injury when extensive, unbalanced NET formation occurs. NETs are embedded with potent granule proteins that are capable of killing pathogens but may also, under the right conditions, induce cell death of lung epithelial and endothelial cells (27) and contribute to certain lung diseases such as asthma (28), cystic fibrosis (29), and COPD (30). Little is known regarding the interaction between NETs and specific cells, including AMs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Because many of the antimicrobial contents of neutrophil extracellular traps (NETs) have intrinsic cytotoxic activity, they also have the potential to cause bystander injury to host cells. [3][4][5][6] However, more recent work has demonstrated that NETs also form in response to noninfectious tissue injury. [3][4][5][6] However, more recent work has demonstrated that NETs also form in response to noninfectious tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…2 In the lung, this has been suspected during infectious exacerbations of cystic fibrosis (CF), chronic pulmonary obstructive disease, bacterial pneumonia, and tuberculosis. [3][4][5][6] However, more recent work has demonstrated that NETs also form in response to noninfectious tissue injury. NETs have been reported to promote inflammation in models of primary lung graft dysfunction (PGD), 7 transfusion-related acute lung injury, 8 and ventilation-induced acute lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…NET primarily identified, produced by neutrophils to kill microorganisms and to defend against pathogens, are demonstrated to be formed also during inflammatory events, as for example, in cystic fibrosis, thrombosis, and chronic obstructive pulmonary disease . In the last years, the list of diseases in which these neutrophil products are demonstrated to be involved was certainly increased and a key role of NET in non‐infective diseases was recently outlined .…”
Section: Discussionmentioning
confidence: 99%